Cloning and expression of recombinant purine nucleoside phosphorylase in the methylotrophic yeast Pichia pastoris - Jaloliddin Abdurakhmanov; Sobirdjan Sasmakov; Shukhrat Khasanov; Oybek Ashirov; Farkhod Eshboev; Khayotjon Dolimov; Saodat Gaynazarova; Tulkin Sadullaev; Oygul Yarilkaganova; Khusan Nasriddinov; Asadali Baymirzaev; Artyom Makhnyov; et al. (Journal of Advanced Biotechnology and Experimental Therapeutics, 2023)
Purine Nucleoside Phosphorylase (PNP) is an enzyme involved in biosynthetic pathway of purine nucleosides. Purine nucleoside phosphorylase catalyzes the cleavage of the glycosidic bond of ribo- or deoxyribonucleosides to form the purine base and deoxyribose- or ribose-1-phosphate. The reversible reaction catalyzed by recombinant PNP of E. coli (EcPNP) has been successfully used for the synthesis of nucleoside analogues. For expression of recombinant EcPNP in Pichia pastoris we have cloned a new recombinant plasmid DNA pPICZαA-PNP (4256 bp), containing the deoD gene (720 bp) amplified from E. coli strain RKMUz-221. The substrate specificity of the recombinant EcPNP expressed in yeast cells was studied by hydrolysis of inosine (9-beta-D-ribofuranosylhypoxanthine) to hypoxanthine and 2-deoxy-β-D-ribofuranosyl. It is established that the obtained recombinant EcPNP (≈28 kD) exhibits high hydrolytic activity and can be used for enzymatic transglycosylation of purine type nucleosides. [ J Adv Biotechnol Exp Ther 2023; 6(3.000): 610-621]